Cross-Cultural Distance Dialogues in Counselor Education: Collaborative Pedagogy - Sarah N Baquet; Jehan Hill (Teaching and Supervision in Counseling, 2022)
Researchers examined the experience of participating in Cross Cultural Distance Dialogues (CCDD) in facilitating Multicultural and Social Justice Counseling Competency (MSJCC) through an interpretive phenomenological analysis (IPA). With the high need to develop curriculum in counselor education programs that intentionally incorporate cultural competencies (Ratts et al., 2016), this study was conducted to explore an innovative pedological technique that further fosters MSJCC within master's level coursework. Four counseling students engaged in a structured dialogue across university campuses during their multicultural course were selected for participation in this study. After completing two rounds of interviews and a member check, the following themes were identified utilizing IPA methodology: (1) relational resistance, (2) negotiating dichotomy, (3) therapeutic space, (4) trust and, (5) cultural awakening. Findings highlight CCDD as an innovative collaborative teaching strategy that supports increased cultural awareness, competency development, and enhanced interpersonal skills and support.
Keywords: phenomenology; collaborative pedagogy; MSJCC; counselor education